GUGATAN NAFKAH ANAK OLEH IBU SETELAH PERCERAIAN DI PENGADILAN AGAMA PADANG - Susan Yuliani, Mardius dan (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
A fact in the existence of living things on earth is that they consist of two types, namely men and women. The two living things, both physically and psychologically have different characteristics, but biologically the two types of living things need each other so that pairing is literally called marriage. Based on the results of the research, it can be concluded that: The judge's considerations granted the claim for alimony by the mother after the divorce that based on Article 41 letter (b) of Law Number 1 of 1974 it is stated that as a result of the breakup of a marriage due to divorce, the father is responsible for all maintenance costs and the child's education required by the child, thus the defendant deliberately did not come to let his civil rights not be defended, then based on Article 149 the lawsuit was granted with vertek. The legal consequences of claims for child maintenance by the biological mother after the divorce are that the obligation of the father and mother to care for and provide maintenance for the child still continues even though both parents have divorced. Compilation of Islamic Marriage Laws regarding child rearing Article 156 (d) in the event of a divorce all costs of hadhanah and child support are the responsibility of the father until he reaches the age of 21